China as Number One? The Emerging Values of a Rising Power - Zhong, Yang (China Understandings Today, 2024)
One of the most significant global events in the last forty years has been the rise of China- economically, technologically, politically, and militarily. The question on people's minds for decades has been whether China will replace the United States as a superpower in the near future. But for China, this power must be comprehensive - having strong economic and militant forces are only two pieces of the puzzle. China must also possess soft power, such as attractive ideologies, values, and culture. China as Number One? explores China's soft powers through the eyes of Chinese citizens. Utilizing data from the World Values Survey, the contributors to this collection analyze the potential soft power of a rising China by examining its residents' social values. A comprehensive study of changes and continuities in the political and social values of Chinese citizens, the book examines findings in the context of evolutionary modernization theory and cross-national comparison.